166k views
4 votes
Please help me with these problems.

Please help me with these problems.-example-1
User Fourier
by
4.6k points

1 Answer

3 votes

Answer:

15. The numbers 3,-6, 12, -24,...

16. The numbers -3, -1,5, 23,...

17, The numbers 3, 9, 15, 21,...

18.
\sum_(n=1)^(\infty) 4((1)/(2))^(n-1)

19. The sum is 8

20.
a_(10)=-12

Explanation:

Question 15:

For the recursive sequence
a_1=3, a_n=a_(n-1)*(-2)


a_1=3,\\a_2=3(-2)=-6\\a_3=-6(-2)=12\\a_4=12(-2)=-24

Therefore we get the numbers: 3, -6, 12, -24, ...

Question 16:

For the sequence
a_n=3^(n-1)-4


a_1=-3\\a_2=-1\\a_3=5\\a_4=23

Therefore we have the numbers -3, -1, 5, 23, ....

Question 17.

For the recursive equation
a_n=a_(n-1)+6


a_1=3


a_2=3+6=9


a_3=9+6=15


a_4=15+6=21

The numbers generated are 3, 9, 15, 21,...

Question 18.

In the series
(4,2,1,(1)/(2),... )

each following number is
(1)/(2) the previous number. The first term is 4, and the sequence has infinite terms; therefore, we have


\sum_(n=1)^(\infty) 4((1)/(2))^(n-1)

Question 19.


\sum_(n=1)^(\infty) 4((1)/(2))^(n-1)=4*\sum_(n=1)^(\infty) ((1)/(2))^(n-1)

since


\sum_(n=1)^(\infty) ((1)/(2))^(n-1)=1-(1)/(2^(n-1))

as n approaches infinity


\lim_(n \to \infty) 1-(1)/(2^(n-1))=1

therefore we have


\sum_(n=1)^(\infty) 4((1)/(2))^(n-1)=4*\sum_(n=1)^(\infty) ((1)/(2))^(n-1)=4*1=4


\boxed{\sum_(n=1)^(\infty) 4((1)/(2))^(n-1)=4}

The sum is 4.

Question 20.

an arithmetic sequence has the form


a_n=a_1+(n-1)d

In our case
a_1=6 and
d=-2; therefore we have


a_n=6-2(n-1)

The 10th term of this sequence would be


a_(10)=6-2(10-1)=6-2(9)=-12


\boxed{a_(10)=-12}

User Mitchell
by
6.1k points